2019
DOI: 10.3892/ol.2019.10719
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nomogram for overall survival in upper aerodigestive tract extranodal natural killer/T‑cell lymphoma, nasal type, stages IE and IIE: A SEER‑based study

Abstract: The present study aimed to develop a widely accepted prognostic nomogram for stage IE and IIE extranodal natural killer/T-cell lymphoma (ENKTCL) of the upper aerodigestive tract by using the Surveillance, Epidemiology, and End Results program database. A total of 396 patients with ENKTCL were included in the present study and were divided into training (n=280) and validation (n=116) cohorts. The Kaplan-Meier method and Cox regression model were used to evaluate the prognostic value of multiple clinical paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Although the impact of these independent prognostic factors has been reported, there is a lack of a predictive model that can incorporate these factors into the analysis simultaneously. In recent years, nomograms had been applied to types of cancer as an extremely effective prediction model for predicting patient's survival (30). In this study, the ROC and DCA results indicated nomogram have better predictive performance compared to TNM-stage.…”
Section: Discussionmentioning
confidence: 71%
“…Although the impact of these independent prognostic factors has been reported, there is a lack of a predictive model that can incorporate these factors into the analysis simultaneously. In recent years, nomograms had been applied to types of cancer as an extremely effective prediction model for predicting patient's survival (30). In this study, the ROC and DCA results indicated nomogram have better predictive performance compared to TNM-stage.…”
Section: Discussionmentioning
confidence: 71%